A two-layer skin construct consisting of a collagen hydrogel reinforced by a fibrin-coated polylactide nanofibrous membrane - Bacakova M (Dove Medical Press, 2019)
Marketa Bacakova,*,1 Julia Pajorova,*,1,2 Antonin Broz,1 Daniel Hadraba,1,3 Frantisek Lopot,3 Anna Zavadakova,4 Lucie Vistejnova,4 Milan Beno,5 Ivan Kostic,6 Vera Jencova,7 Lucie Bacakova11Department of Biomaterials and Tissue Engineering, Institute of Physiology of the Czech Academy of Sciences, Prague, Czech Republic; 22nd Faculty of Medicine, Charles University, Prague, Czech Republic; 3Department of Anatomy and Biomechanics, Faculty of Physical Education and Sport, Charles University, Prague, Czech Republic; 4Biomedical Center, Medical Faculty in Pilsen, Charles University, Pilsen, Czech Republic; 5Institute of Experimental Endocrinology, Biomedical Research Center of the Slovak Academy of Sciences, Bratislava, Slovak Republic; 6Institute of Informatics, Slovak Academy of Sciences, Bratislava, Slovak Republic; 7Department of Chemistry, Technical University of Liberec, Liberec, Czech Republic*These authors contributed equally to this workBackground: Repairs to deep skin wounds continue to be a difficult issue in clinical practice. A promising approach is to fabricate full-thickness skin substitutes with functions closely similar to those of the natural tissue. For many years, a three-dimensional (3D) collagen hydrogel has been considered to provide a physiological 3D environment for co-cultivation of skin fibroblasts and keratinocytes. This collagen hydrogel is frequently used for fabricating tissue-engineered skin analogues with fibroblasts embedded inside the hydrogel and keratinocytes cultivated on its surface. Despite its unique biological properties, the collagen hydrogel has insufficient stiffness, with a tendency to collapse under the traction forces generated by the embedded cells.Methods: The aim of our study was to develop a two-layer skin construct consisting of a collagen hydrogel reinforced by a nanofibrous poly-L-lactide (PLLA) membrane pre-seeded with fibroblasts. The attractiveness of the membrane for dermal fibroblasts was enhanced by coating it with a thin nanofibrous fibrin mesh.Results: The fibrin mesh promoted the adhesion, proliferation and migration of the fibroblasts upwards into the collagen hydrogel. Moreover, the fibroblasts spontaneously migrating into the collagen hydrogel showed a lower tendency to contract and shrink the hydrogel by their traction forces. The surface of the collagen was seeded with human dermal keratinocytes. The keratinocytes were able to form a basal layer of highly mitotically-active cells, and a suprabasal layer.Conclusion: The two-layer skin construct based on collagen hydrogel with spontaneously immigrated fibroblasts and reinforced by a fibrin-coated nanofibrous membrane seems to be promising for the construction of full-thickness skin substitute.Keywords: full-thickness skin substitutes, collagen hydrogel, fibroblast and keratinocyte co-cultivation, fibrin, nanostructure